Referenciação multimodal: a construção de objetos-de-discurso no jornal impresso Folha de S. Paulo - Cíceri de Oliveira, Natalia Santos [UNESP] (2015)
This research aims at analyzing the referencial process, considering the relation between verbal and nonverbal elements in the newspaper. Specifically, we examine the elaboration of referents in the articulation of two elements that constitute the features of Folha de S. Paulo newspaper: the picture(s) and a highlighted noun phrase in the composition. Based on the characterization of this process called mutual (re)categorization, auxiliary processes that works in the referential construction are considered. In order to achieve our goals it was made a thematic approach focusing reference to discourse objects belonging to the category of public figure. To constitute the corpus, it was considered compositions from the newspaper front page and inside pages. It was demonstrated that analyzing the newspaper referencing brings into question the constitution of this support, which dynamic interferes directly in the way public figure is represented. The theoretical underpinnings used in this study are from social-cognitive-interactionist Textual Linguistics, that takes the referenciation as discursive activity, situated in social practices of the subjects and built in an specific interactional context (MONDADA; DUBOIS, 2003; KOCH, 2005), and from Grammar of Visual Design (KRESS; VAN LEEUWEN, 2006), which proposal, allied to Social Semiotics, present a description model of different modalities. Some considerations from authors of communication are also brought, in order to discuss issues related to the newspaper, as the layout and typography. The results point that verbal and nonverbal elements, articulated by the layout, work in a dynamic way in the referent construction